Flora and fauna of the West and the East in the diary of Oles Honchar - Галич, Олександр Андрійович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
The fate presented to the Ukrainian writer Oles’ Honchar, whose 100th anniversary was celebrated in April 2018, to visit different continents of the world, to get acquainted with the history and culture of the states of the West and the East, to see the peculiarities of their nature. The naturalistic space of the diaries by Oles’ Honchar reaches not only Ukraine and the former Soviet Union, but also a dozen states of the West and the East, which Ukrainian writer managed to visit. Writing about the flora and fauna of the USA, Japan, India, Indonesia and other countries of the world, the writer pays attention to the peculiarities of the flora and fauna, noting it’s exotic origin, sometimes comparing it with Ukrainian nature. Observations of plants, animals, birds and insects of foreign countries often reflect the mood of the author, are coherent with his experiences, thoughts, creative plans, their implementation. Separate records that reproduce the flora and the fauna, are finished artistic miniatures with a pronounced imagery, metaphor, associativity.